Kita harus berubah! : analisis ekonomi Faisal Basri - Basri, Faisal H., 1959- (Penerbit Buku Kompas, 2005)
Need changes towards quality of good governance by eliminating corrupt practices and accumulated loans in Indonesia; collected articles previously published in Kompas newspaper.